Quantitative assessment of bio-aerosols contamination in indoor air of University dormitory rooms - Hayleeyesus, Samuel Fekadu; Ejeso, Amanuel; Derseh, Fikirte Aklilu (International Journal of Health Sciences, 2015)
Objectives: The purpose of this study is to provide insight into how students are exposed to indoor bio-aerosols in the dormitory rooms and to figure out the major possible factors that govern the contamination levels. Methodology: The Bio-aerosols concentration level of indoor air of thirty dormitory rooms of Jimma University was determined by taking 120 samples. Passive air sampling technique; the settle plate method using open Petri-dishes containing different culture media was employed to collect sample twice daily. Results: The range of bio-aerosols contamination detected in the dormitory rooms was 511- 9960 CFU/m3 for bacterial and 531- 6568 CFU/m3 for fungi. Based on the criteria stated by WHO expert group, from the total 120 samples 95 of the samples were above the recommended level. The statistical analysis showed that, occupancy were significantly affected the concentrations of bacteria that were measured in all dormitory rooms at 6:00 am sampling time (p-value=0.000) and also the concentrations of bacteria that were measured in all dormitory rooms were significantly different to each other (p-value=0.013) as of their significance difference in occupancy (p-value=0.000). Moreover, there were a significant different on the contamination level of bacteria at 6:00 am and 7:00 pm sampling time (p=0.015), whereas there is no significant difference for fungi contamination level for two sampling times (p= 0.674). Conclusion: There is excessive bio-aerosols contaminant in indoor air of dormitory rooms of Jimma University and human occupancy produces a marked concentration increase of bacterial contamination levels and most fungi species present into the rooms air of Jimma University dormitory were not human-borne. Key words: indoor air, bio-aerosol, bacteria, fungi, sedimentation technique, dormitory room.